Calibration of two mathematical models at laboratory scale for predicting the generation of methane and carbon dioxide at the entrance point of the Chucurí river to the Topocoro Reservoir, Colombia (2019)
(Eng) Reservoirs emit greenhouse gases (GHGs) as a result of flooded organic matter biodegradation after the filling process or the organic matter that enters through the tributaries. Hence, it is important to take an inventory of greenhouse gas emissions in the reservoirs, so that, measures can be established to minimize the impact of global warming. These gases are produced by anaerobic or aerobic processes occurring in reservoirs. In this work, the formation rates of carbon dioxide (CO2) and methane (CH4) in anaerobic reactors in batch were evaluated at laboratory scale, using water and plant material from the Topocoro reservoir, located in the department of Santander-Colombia. The results showed degradation rates of 0.5843 mg O2/L.d and 0.1269 mg O2/L.d for dissolved and particulate organic matter respectively. Furthermore, gas emissions after completing the degradation time were 0.6269 mg CH4/L and 31.2443 mg CO2/L. It was implemented a linear model to predict the formation of CO2 and an exponential model to predict the formation of CH4 with determination coefficients of 0.9999 and 0.9928 respectively. .